Long live the American dream: Self-selection and inequality-persistence among American immigrants - Joakim Ruist (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
This paper aims to explain the slow economic convergence between groups of different ancestries in the US, i.e. why these groups experience even less intergenerational mobility than individuals in the same country. It shows how excessively persistent inequality may be a long-lasting outcome of ancestors' self-selection into migration, and need not involve e.g. ethnicity-based behaviors. A testable implication is that the correlation between home country characteristics that influence self- election, and migrants' and their descendants' outcomes should increase generation by generation. Verifying this, their ancestors' migration distance has risen to explain around half the inequality between fourth-generation immigrant groups today.
Keywords: F22; I24; J61; J62; 330; migration; selection; intergenerational mobility; ancestry; immigrant integration